Exploration of the endo‐lysosomal pathway genes in frontotemporal dementia: The use of protein‐protein interaction networks to prioritize rare‐variant association analysis results: Genetics/molecular genetics. (7th December 2020) - Kocoglu, Cemile; Manzoni, Claudia; Ferrari, Raffaele; Van Broeckhoven, Christine; van der Zee, Julie
Abstract: Background: Genetic studies in frontotemporal dementia (FTD) have identified multiple genes linked to the disease, yet explain only 30% of the patients. Identification of genetic causes in the remaining inherited cases is needed to elucidate the molecular biology of disease development, and thereby to pinpoint novel targets for therapeutic applications. Multiple lines of evidence have demonstrated disruption of the endo‐lysosomal pathway (ELP) in dementia. Here, we aimed to search for novel FTD genes in the ELP through rare variant association analysis. Method: We applied weighted protein‐protein interaction (PPI) network mapping using 66 dementia‐associated genes (FTD, Alzheimer disease and Lewy‐body dementia) as seed genes. From this 'Dementia interactome', we extracted brain expressed ELP associated genes consulting Gene Ontology, Reactome, GTEx and Braineac. Exome‐wide rare variant association was tested using SKAT‐O, CMC and Madsen‐Browning tests. Result: We generated whole exome sequencing data on 238 Belgian FTD patients and extracted exonic variants from whole genome sequencing data of 176 Belgian controls, obtained through collaboration with Project MinE (van der Spek et al., 2019). No genes passed exome‐wide significance level in the rare‐variant burden tests. Mapping ELP‐associated genes on the PPI network resulted in a list of 2.486 genes to be prioritized in our gene burden test results. As a result of this prioritization, 31 genes reached nominal significance. We are presently investigating those genes by incorporating their weight in the network (i.e. distance to known gene products and network topology), as genes with a higher weight are more likely contributors to disease development. Preliminary results suggest a role for vesicle‐mediated transport (GO:0016192) genes in FTD risk. Conclusion: Applying a tailored PPI network approach, we prioritized ELP‐associated genes as potential disease (risk/protective) genes for FTD. ELP candidate genes pointed towards a role for vesicle‐mediated transport in FTD pathogenesis. This prioritization approach increases the power needed for rare variant disease association. Furthermore, we present an accessible disease pathway‐based analysis pipeline that is applicable to different types of genetic studies (rare high‐penetrant vs common‐risk) and disease phenotypes and pathways of interest.